Ferroptosis in plants: triggers, proposed mechanisms and the role of iron in modulating cell death - Distefano, Ayelen Mariana (2020)
Regulated cell death plays key roles during essential processes along the plant life cycle. It takes part of specific developmental programs and maintains the organism homeostasis in response to unfavorable environments. Ferroptosis is a recently discovered iron-dependent cell death pathway characterized by the accumulation of lipid reactive oxygen species. Ferroptosis in plants shares all the main hallmarks described for ferroptosis in other systems. Those specific features include biochemical and morphological signatures that seem conserved among species. However, plant cells have specific metabolic pathways and a high degree of metabolic compartmentalization. Together with their particular morphology, these features add more complexity to the plant ferroptosis pathway. In this review, we summarize the most recent advances in elucidating the roles of ferroptosis in plants, focusing on specific triggers, main players and underlying pathways.